Pengurusan Fatwa Di Negara-Negara Nusantara: Negara Brunei Darussalam - Syed Salim Syed Shamsuddin; Muhammad Mustaqim Mohd.Zarif; Mushaddad Hasbullah (Universiti Sains Islam Malaysia, 2024)
This study focuses on identifying and analyzing issues and aspects relating to the management and development of fatwa and the Mufti institution in Negara Brunei Darussalarn. At the same time, matters relating to the history, organization and administration of fatwa affairs in Brunei h mth e past until the present day will also be discussed for a more comprehensive view and understanding of the subject matter. As such, this research is primarily based on the library research method and observations based on the available documented evidences and works written on the subject. Tbe findings indicate that the commitment and enthusiasm showed by the d e r and people of Brunei to uphold the institution of fatwa and Mufti at the national level has made it as an important entity with influence over the state's national and administrative policies. In addition, the efficiency and systematic administration of the State Mufti Department through the use of the latest technological advancement in telecommunications technology in disseminating fatwa is exemplary for other Muslim countries, especially in matters relating to the management of fatwa affairs.